Chromosomal Rearrangements in Salmonella enterica Serovar Typhi Strains Isolated from Asymptomatic Human Carriers - T. David Matthews (American Society for Microbiology, 2011)
ABSTRACT Host-specific serovars of Salmonella enterica often have large-scale chromosomal rearrangements that occur by recombination between rrn operons. Two hypotheses have been proposed to explain these rearrangements: (i) replichore imbalance from horizontal gene transfer drives the rearrangements to restore balance, or (ii) the rearrangements are a consequence of the host-specific lifestyle. Although recent evidence has refuted the replichore balance hypothesis, there has been no direct evidence for the lifestyle hypothesis. To test this hypothesis, we determined the rrn arrangement type for 20 Salmonella enterica serovar Typhi strains obtained from human carriers at periodic intervals over multiple years. These strains were also phage typed and analyzed for rearrangements that occurred over long-term storage versus routine culturing. Strains isolated from the same carrier at different time points often exhibited different arrangement types. Furthermore, colonies isolated directly from the Dorset egg slants used to store the strains also had different arrangement types. In contrast, colonies that were repeatedly cultured always had the same arrangement type. Estimated replichore balance of isolated strains did not improve over time, and some of the rearrangements resulted in decreased replicore balance. Our results support the hypothesis that the restricted lifestyle of host-specific Salmonella is responsible for the frequent chromosomal rearrangements in these serovars. IMPORTANCE Although it was previously thought that bacterial chromosomes were stable, comparative genomics has demonstrated that bacterial chromosomes are dynamic, undergoing rearrangements that change the order and expression of genes. While most Salmonella strains have a conserved chromosomal arrangement type, rearrangements are very common in host-specific Salmonella strains. This study suggests that chromosome rearrangements in the host-specific Salmonella enterica serovar Typhi, the causal agent of typhoid fever, occur within the human host over time. The results also indicate that rearrangements can occur during long-term maintenance on laboratory medium. Although these genetic changes do not limit survival under slow-growth conditions, they may limit the survival of Salmonella Typhi in other environments, as predicted for the role of pseudogenes and genome reduction in niche-restricted bacteria.